The Effects of Persian Medicine on Knowledge, Attitude, and Practice of Medical Sciences Students - Mohammad Ebrahim Zohalinezhad; Mohammad Hasan Keshavarzi; Masoud Karimi; Maral Ostovarfar; Ahmad Dadmehnia; Seyed Aliakbar Faghihi (Shiraz University of Medical Sciences, 2024)
Background: Traditional medicine refers to a set of indigenous or acquired health care practices outside the mainstream health care system in any country. A wide range of people use traditional and complementary medicine in Iran, and due to its ancient Persian origin, it is known as Persian Medicine (PM). PM is used for a wide range of people and diseases because it comprises various treatment strategies. Thus, the familiarity of healthcare providers with it seems essential for them.Methods: This quasi-experimental study was conducted to investigate the effect of PM education on the knowledge, attitude, and practice of medical sciences students in Iran. In this study, an educational intervention on knowledge, attitude, and practice of Persian medicine was conducted on medical sciences students in the fifth-largest region of health education in Iran. The data were collected from 99 medical sciences students. The knowledge of these participants was evaluated and compared before and after the courses by a questionnaire scored using 5-point Likert scale.Results: The mean score of selected students was 25.28 before starting the course, but after completing the course, their mean score of knowledge changed significantly and reached 31.03. Although, after the course, the use and attitude of theseparticipants increased, these rises were statistically significant in a few items.Conclusion: Overall, the findings of our study indicated that this course had a practical impact on medical science students' knowledge, practice, and attitude toward PM. Accordingly, this course will improve the insight of future healthcare providers about PM.